2024
DOI: 10.1037/dev0001589
|View full text |Cite
|
Sign up to set email alerts
|

Friendship trajectories and health across the lifespan.

Kristine J. Ajrouch,
Rita Xiaochen Hu,
Noah J. Webster
et al.

Abstract: Friends are a vital source of social relations throughout the lifespan and across developmental stages. Our knowledge of how friendships develop over time, especially from childhood through adulthood, is limited. Furthermore, it is now recognized that this specific type of relationship influences health across the life course in unique ways. Using the Convoy Model of Social Relations as a guiding framework, this study charts the multiple and unique trajectories of friendship across adulthood and tests whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Yet, examining trends from the general social survey from 1970 to 2010, Fischer [ 16 ] concluded that Americans “were no more and no less likely to be friendless” and “had roughly the same median number of friends,” although he concedes that “recent cohorts may not have been as likely to have as many friends” (p. 60). Similarly, a recent report from Ajrouch et al [ 17 ] pushed back on the narrative that friendship network size declines with age. A reduction in the number of friends and discussion partners has been challenged [ 18 , 19 ], and may be a product of methodological artifacts [ 20 ], wherein how the data is collected (and questions framed) influenced estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, examining trends from the general social survey from 1970 to 2010, Fischer [ 16 ] concluded that Americans “were no more and no less likely to be friendless” and “had roughly the same median number of friends,” although he concedes that “recent cohorts may not have been as likely to have as many friends” (p. 60). Similarly, a recent report from Ajrouch et al [ 17 ] pushed back on the narrative that friendship network size declines with age. A reduction in the number of friends and discussion partners has been challenged [ 18 , 19 ], and may be a product of methodological artifacts [ 20 ], wherein how the data is collected (and questions framed) influenced estimates.…”
Section: Introductionmentioning
confidence: 99%